The Effects Of Derivatives, Commitments and Contingencies on Banking Risk with Capital Adequacy Ratio As A Moderating Variable - Aeniyatul Muhaqiyah; Rimi Gusliana Mais; Harry Indradjit Soeharjono (Indonesian Journal of Business, Accounting and Management (IJBAM), 2019)
Abstract— This study aims to examine the effect of derivatives, commitments and contingencies on bank risk with Capital Adequacy Ratio as a moderating variable on banking companies listing on the Indonesia Stock Exchange (IDX). This research is a quantitative study, which is measured using a panel data regression based method with eviews 10 . The population of this research is banking companies listing on the Indonesia Stock Exchange (IDX) in 2013-2018. The sample is determined based on the purposive sampling method, with a sample of 32 banking companies so that a total of 192 observations. The data used in this study are secondary data. The data collection technique using the method of documentation via the official website IDX: www.idx.co.id . Hypothesis testing using t test. The results of the research prove that: (1) Derivatives have a negative effect on bank risk which means that derivatives are used by banks for hedging. (2) Commitment has a positive effect on bank risk which means that the commitment of lending at certain interest rates increases the dependence on interest rate volatility so that the use of commitments will increase risk. (3) However, contingencies are proven to have no effect on bank risk because they are used as collateral (contingencies) as a direct substitute for credit so that the counterparty is less likely to commit violations, so this does not affect bank risk. (4) Capital Adequacy Ratio is proven to weaken the negative influence of derivatives on bank risk which means that the CAR determined by the bank is intended to stabilize bank risk so that the CAR will weaken the risk reduction due to derivative transactions. (5) Capital Adequacy Ratio is also proven to be able to weaken the positive influence of commitments on bank risk which means that CAR functions more to stabilize risk, namely when a committed transaction increases risk, CAR will weaken the increase in risk. (6) However, the Capital Adequacy Ratio is proven to be unable to weaken the positive effect of contingencies on bank risk, which means that there is a balance between administrative activities (contingencies) and reserves carried out so that they are not exposed to risk.